Intuitions 2014
DOI: 10.1093/acprof:oso/9780199609192.003.0002
|View full text |Cite
|
Sign up to set email alerts
|

The Rational Roles of Intuition

Abstract: Intuitions are often thought of as inputs to theoretical reasoning. For example, you might form a belief by taking an intuition at face value, or you might take your intuitions as starting points in the method of reflective equilibrium. The aim of this paper is to argue that in addition to these roles intuitions also play action--guiding roles. The argument proceeds by reflection on the transmission of justification through inference. According to inferential internalists, in order to gain justification for be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…24 Thanks to the editors for raising this point. 25 This abstracts away from the possibility that inference involves an additional intentional state like an intuition (Chudnoff, 2014), which is not relevant to the distinction between belief and seemings. 26 Modern dual-component views appear especially committed to the claim that seemings require the construction of an additional representation when one considers the putative epistemological function of seemings on (at least some of) these views.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Thanks to the editors for raising this point. 25 This abstracts away from the possibility that inference involves an additional intentional state like an intuition (Chudnoff, 2014), which is not relevant to the distinction between belief and seemings. 26 Modern dual-component views appear especially committed to the claim that seemings require the construction of an additional representation when one considers the putative epistemological function of seemings on (at least some of) these views.…”
Section: Resultsmentioning
confidence: 99%
“…This abstracts away from the possibility that inference involves an additional intentional state like an intuition (Chudnoff, ), which is not relevant to the distinction between belief and seemings.…”
mentioning
confidence: 99%
“…But other interpretations are also possible. Some philosophers have suggested that taking is a representational state which falls short of belief, such as an intuition, understood as a kind of intellectual seeming (Chudnoff , Tucker ). Others have suggested that taking is a sui generis state (Boghossian , Hlobil ms).…”
Section: Preliminariesmentioning
confidence: 99%
“…Besides Boghossian, defenders of the Taking Condition include Tucker (), Neta (), Broome (), Chudnoff (), Valaris (forthcoming), and Hlobil (ms).…”
mentioning
confidence: 99%
See 1 more Smart Citation